2014
DOI: 10.1016/j.celrep.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Contribute to Generation of Adult Ventricular Myocytes during Cardiac Homeostasis

Abstract: SUMMARY Cardiac tissue undergoes renewal with low rates. Although resident stem cell populations have been identified to support cardiomyocyte turnover, the source of the cardiac stem cells and their niche remain elusive. Using Cre/Lox-based cell lineage tracing strategies, we discovered that labeling of endothelial cells in the adult heart yields progeny with cardiac stem cell characteristics that express Gata4 and Sca1. Endothelial-derived cardiac progenitor cells were localized in the arterial coronary wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 54 publications
3
49
1
Order By: Relevance
“…Furthermore, the findings are in agreement with previous reports supporting the existence of cKit + CPs, which do not contribute to coronary endothelium (15), as well as with recent endothelial lineage fate-mapping analyses suggesting that the coronary endothelium is unlikely to originate from cKit + cells (6,29).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, the findings are in agreement with previous reports supporting the existence of cKit + CPs, which do not contribute to coronary endothelium (15), as well as with recent endothelial lineage fate-mapping analyses suggesting that the coronary endothelium is unlikely to originate from cKit + cells (6,29).…”
Section: Discussionsupporting
confidence: 82%
“…Our study differs from a recent cardiac genetic fate-map of cKit, using different cKit alleles (21). First, in contrast to findings presented here and elsewhere (6,15,29), van Berlo et al (21) reported that cKit CPs contribute extensively to coronary endothelium. However, it is noteworthy that mutations in the mouse W/cKit locus have not been associated with tangible cardiovascular defects (12), as would be likely if cKit + CPs comprised a major source of coronary vascular cells.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Hence, the true extent to which these Sca-1 lineage–traced CPCs contribute new cardiomyocytes to the heart remains uncertain. Moreover, recent lineage-tracing studies using endothelial drivers of Cre recombinase showed at least transient expression of Sca-1 on perivascular cells that eventually became cardiomyocytes, suggesting that Sca-1–expressing cells in the heart may simply be endothelial progenitors 32 . Importantly, there is no orthologous counterpart of Sca-1 in humans, thereby precluding isolation and therapeutic strategies based on Sca-1 as a cellular marker in humans.…”
Section: Cellular Sources Of Adult Cardiac Regenerationmentioning
confidence: 99%
“…This inconsistency has been shown in previous studies, which variably support 18, 21, 29 or refute endothelial cell 16, 35 differentiation capacity of cKit cells. Similarly, most studies document that coronary endothelium-producing cells do not express cKit 3739 .…”
Section: The Identity Of Ckit+ Cell Lineage(s) In the Heartmentioning
confidence: 99%